Uso do grau de preferência alimentar para a caracterizaç ão da alimentação de peixes na APA de São Pedro e Analândia - Muller Gomiero, Leandro [UNESP]; De Souza Braga, Francisco Manoel [UNESP] (Universidade Estadual de Maringa, 2005)
We studied feeding habits of four fish species in two watershed at APA - Área de Proteção Ambiental (Area of Environmental Protection) in São Pedro and Analândia, State of São Paulo, southeastern Brazil. Feeding Preference Degree (FPD) was used to demonstrate the importance of each food item for the species of both basins. Feeding habits of both species of lambari was variable. The allochtonous items such as insects, autochtonous items, and vegetal material were very important, characterizing omnivory. The bagre (Rhamdia quelen) fed mainly on insects at the Jacaré-pepira Basin and also on fishes at the Corumbataí basin. The cascudo Hypostomus strigaticeps ingested autochtonous vegetal material and sediments at both basins.
The use of feeding preference degree to characterize feeding habits of fishes at APA in São Pedro and Analândia
Keywords: APA of São Pedro and Analândia; Feeding habits; Feeding preference; Fishes; Brazil; environmental protection; feeding behavior; fish; nonhuman; omnivory; sediment; species differentiation; taste preference; vegetable; watershed; Bagre; Hexapoda; Hypostomus; Pisces; Rhamdia quelen